School‐to‐work transition and subjective well‐being in Australia. (22nd September 2021) - Dietrich, Hans; Patzina, Alexander; Chesters, Jenny; Reissner, Volker
Abstract: The school‐to‐work transition is a demanding period during an individual's life course in all societies particularly because the educational decisions made during this period have long‐lasting consequences in multiple life domains. Moreover, adverse starting points after secondary school are likely to lead to adverse outcomes that might cumulate over the life course. This study analyses subjective well‐being during this sensitive period and examines the following two questions. First, how do different school‐to‐work transitions relate to subjective well‐being changes? Second, how does subjective well‐being develop during and after secondary schooling? As the school‐to‐work transition period is structured by gender, each analytical step aims to identify gender differences. Furthermore, based on life course theories, this study investigates whether adverse starting points after secondary school lead to cumulative effects in the development of subjective well‐being. Based on data from the Household, Income and Labour Dynamics in Australia (HILDA) survey and fixed effects regressions, our results reveal that transitions to employment increase subjective well‐being, while transitions to unemployment decrease subjective well‐being. Furthermore, transitions to study increase subjective well‐being only among men, while such transitions appear to decrease subjective well‐being among women. The results related to the development of subjective well‐being indicate that subjective well‐being decreases during secondary schooling and continues to decrease after individuals leave school. This decrease is stronger among men. Finally, our results reveal the negative cumulative effects of adverse starting points on the development of subjective well‐being. Overall, the results reveal great intra‐individual variation in subjective well‐being during the school‐to‐work transition period in Australia.